An Analysis of Student’s Errors in the Use of Simple Present Tense at the Eight Student of SMP Islam Pancor Kopong - Ridho Atul Jannah; Rini Marliana; Himni, M. Saleh (LPPM Institut Studi Islam Sunan Doe, 2023)
This paper aims to know the type errors that happened in speaking daily activities of eight grade of SMP Islam Pancor Kopong. This research used qualitative design. This study was focused on analyzing the type of errors that’s produce by students in simple present tense that have been collected from 15 students of eight grade of SMP Islam Pancor Kopong. The data can be found by spoken test. The researcher ask the student to tell about daily activities. This test should be completed by subjects in order to find out the errors in their speaking. The risults of this research. The researcher found some type of errors such as omission, addition, misformation and misodering. Omission (29 errors = 39.19%), followed by misformation (20 errors = 27.03%), addition (14 errors = 18.92%) and misodering (11 erros = 14.86%).